Circulating miRNAs as independent predictors of cardiovascular mortality in patients with type 2 diabetes mellitus. (3rd October 2022) - Jakubik, D; Eyileten, C; Nowak, A; Wolska, M; Keshwani, D; Jarosz-Popek, J; De Rosa, S; Mirowska-Guzel, D; Siller-Matula, J; Postula, M
Abstract: Background: MicroRNAs (miRNAs, miR) are essential gene expression regulators involved in numerous biological processes and diseases including type 2 diabetes (DM). Purpose: We aimed to determine the predictive value of selected circulating miRNAs for cardiovascular and all-cause mortality and their potential usefulness as biomarkers in DM patients. Method: Two hundred fifty-two patients with diabetes were enrolled in the study. Among the patients included, 26 (10.3%) patients died during a median follow-up of 71 months (5.9 years). Plasma miR-191 and miR-16 expressions were assessed by quantitative real-time PCR and compared between the patients who survived and those who died. Results: Patients who died from cardiovascular-related death had significantly higher expression of miR-191 and miR-16 as compared with patients who survived (p=0.003, p=0.001, respectively). The study population was divided into two subgroups by using ROC curve analysis for each miRNA, i.e., low or high value of single miRNAs. Kaplan Meier and Cox regression were performed for survival analysis. High expression levels of miRNAs were associated with cardiovascular mortality, when the models included one single miRNA and other covariates: miR-191 (HR = 4.793, 95% CI: 1.48–15.579; p=0.009) and miR-16 (HR = 4.66, 95% CI: 1.48–14.75; p=0.009). Furthermore, miRNAs expression between clopidogrel and the whole acetylsalicylic acid groups (i.e., 75 mg +150 mg), miR-191 expressions was significantly higher in the clopidogrel subgroup (p=0.010), whereas miR-16 did not differ (p=0.127). Conclusion: To conclude, miR-191 and miR-16 expression are strong and independent predictors of cardiovascular and all-cause mortality in patients with T2DM. Moreover, miR-191 and miR-16 present significant interactions with antiplatelet treatment regimens and clinical outcomes. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Warsaw